An interpretative phenomenological analysis on the lived experiences of Filipino K-pop merchandise collectors - Marquez, Larissa Faye V. (Animo Repository, 2022)
Collecting is a hobby that collectors perceive as more than just a recreational pursuit as they are also motivated to acquire items to fulfill economic, hedonic, and self-enhancement needs. The rise of the Korean Wave in the Philippines produced a new subset of collectors equally dedicated to their craft yet relatively unexplored—the Filipino K-pop merchandise collectors. This study aimed to investigate their lived experiences through interpretative phenomenological analysis. Data were collected through semi-structured focus group discussions with eight Filipino K-pop collectors. Five master themes were identified: (1) collection leads to a deeper sense of connection with K-pop idols; (2) shaping the collecting experience through an online collecting community; (3) dealing with inevitable resource scarcity; (4) difficulty in overcoming impulse buying; and (5) meaningful collecting experiences encourage long-term commitment. Results showed that through their lived experiences, collectors achieved satisfaction, belongingness, and developed life skills. However, negative experiences from their impulsiveness and involvement in the community also shaped their pursuit. Despite the adversities, their sustained desire to become closer and connected with their idols motivate them to continue collecting merchandise. The current study provides insight into how collecting is a positive and meaningful hobby for the participants because of their connection with their idols and fellow collectors. Implications on healthy coping mechanisms for maintaining and expanding one’s collection and online safety when obtaining collectibles are also discussed. Keywords: collecting, K-pop merchandise, lived experiences, interpretative phenomenological analysis